Communication Patterns and Media Technology Role in Organization and Society During Pandemic - Andhita Vidya Putri; Irwansyah Irwansyah (The Journal of Society and Media, 2020)
Covid-19 pandemic as the background of the Work From Home (WFH) policy is believed to have increased major participation in communication technology and changed communication patterns. The research aims to know the implementation of WFH during the pandemic, the use of communication technology, the communication patterns during WFH have changed from face to face to Computer Mediated Communication (CMC), and the important factors for the success of WFH. A qualitative method with a descriptive case study approach and a semi-structured interview technique are used. The theory is media richness theory. The results showed that WFH offered advantages and disadvantages for employees and organizations. WFH featured various types of technology/media, from lean to rich. Communication technology plays an important role during WFH which causes changes in communication patterns. Different technologies/media vary in its ability to reproduce messages. During WFH, CMC creates a different climate than face to face communication, because CMC is not as rich as face to face communication. In implementing WFH, even after the pandemic, it is necessary to pay attention to the needs of organizations and employees and the main factors of successful WFH implementation so that WFH can be as effective as working in an office.